#TITLE_ALTERNATIVE# - KURNIASIH , ANIS
Ngawi 1 which is consists of cranium was found at teh base of Bengawan Solo River so that the stratigraphic position was unclear. Wajak 1 consists of cranium and facial parts which is also having unknown age because there were never made absolute dating of fossil and rock layer that contained this fossil. This study was conducted to determine similarities and dissimilarities of the fossil samples to determine the direction of evolution. Comparative anatomy analysis performed in this study aimed to compare anatomic features of the entire samples. Anatomic features which are compared include of anatomic morphology (qualitative) and biometric size (quantitative) and then the results of the measurements were statistically analyzed using PCA and cluster methods. In this research, anatomy analysis is held on fossils found in Ngawi that is Ngawi 1 and from Wajak that is Wajak 1, which are compared with the fossils from Sangiran (S10, S12, S17), Bukuran, Sambungmacan (Sm1, Sm3, Sm4) and Ngandong (Ng9, Ng10, Ng11). Ngawi 1 which consists of cranium was found at the base of the Bengawan Solo River so that the stratigraphic position was unclear. From the results of PCA analysis, Ngawi 1 have similar shape and size closest to Sm3 based on values of the parameter parietal chord, maximum cranial length, occipital chord, and maximum cranial breadth. While Wajak1 have different shapes and sizes with most other fossils that is bigger, based on values of the same parameter, which are also shown in cluster analysis. In morphology description, Ngawi1 has similarities with fossil Bapang group (S10, S12, S17, and Bukuran) and Sambungmacan - Ngandong group (Sm1, Sm3, Sm4, Ng9, Ng10, and Ng11). Frontal part possess a supraorbital torus which is thick and prominent and there is a depression in glabela. In addition, Ngawi1 cranial is widening to the posterior, it is also seen in samples of Bapang group and Sambungmacan Ã‚Â– Ngandong group. While Wajak 1, there are no depression in glabela and supraorbital torus tends to thin and not too obtrusive in frontal part, those morphology characteristics are some of the Homo sapiens characteristics. Based on anatomical characteristics (qualitative) and measurement (quantitative,) Ngawi1 can be incorporated into the same group with Homo erectus which was found in Sambungmacan (Sm3) with Pleistocene Lower - Middle Pleistocene age, while Wajak 1 has the smallest similarity with other fossil and separated from Homo erectus. The similarity between Wajak 1 fossil and Homo erectus fossils from Java anatomically is posterior part of occipital bone that was large and increasing in height of temporal bone (heightening) from Homo erectus to Wajak 1 and so the form of cranium be more rounded. Based on that conditions, Wajak 1 has to be separated from Homo erectus in Java, and geologically proved by rock layer or formation contained of Wajak 1 fossil which was younger than rock layer contained of Homo erectus fossils, that is terrace deposite in Lawa Cave which attain the age of Holosen. The evolution pattern of hominids in Java from fossils analyzed in this research showed a development pattern of Archaic Homo erectus which were found in Sangiran (S10, S12, S17, Bukuran) into Tipic Homo erectus which were found in Sambungmacan (Sm1, Sm3, Sm4, Ngawi1) and evolved into Progressive Homo erectus from Ngandong (Ng9, Ng10, Ng11). Later, Progressive Homo erectus evolved into Homo sapiens (Wajak 1), and Homo sapiens evolved into Homo sapiens sapiens (modern human).